INTERROGATING THE CHALLENGING PATHWAYS OF DECENTRALIZATION OF WATER AND SANITATION SERVICES DELIVERY IN THE WA MUNICIPALITY OF THE UPPER WEST REGION OF GHANA - Arthur, D. D. (UDS International Journal of Development, 2018)
Despite the commitments of government and other stakeholders to achieving improved access to water and sanitation services delivery in Ghana, water accessibility is still a problem for a large number of people. In the Wa Municipality of Ghana, the available evidence reveals that a substantial number of households do not have access to water supply and sanitation services. This paper presents a case study design aimed at interrogating the challenging pathways of decentralization of water and sanitation services delivery in the Wa Municipality. Semi-structured interview schedules and questionnaires were used to gather data from sixty participants selected from the study area. Documentary data were also used to complement the data obtained from the field to arrive at the analysis. The issues identified in the study were as follows: Ineffective legislative frameworks, poor institutional procedure for selecting the beneficiary communities, power struggle between the actors at the local level, lack of coordination and collaboration among the external donor agencies, and poor access to available spare parts. A number of issues were found to be indispensable in accelerating progress in the water and sanitation sub-sector. These include the strengthening of the legislative framework regulating the sub-sector, involvement of the community in the projects, provision of better leadership and coordinaÂtion needed in the sub-sector, provision of available spare parts for the communities, and implementation of effective water and sanitation administrative structures at the local levels.Â Â Keywords: Decentralization, Interviews, Water and Sanitation, Wa Municipality, Northern Ghana